Human and robot hands : sensorimotor synergies to bridge the gap between neuroscience and robotics - Bianchi, Matteo; Moscatelli, Alessandro (Springer Series on Touch and Haptic Systems, 2016)
This booklooks at the common problems both human and robotic hands encounter when controllingthe large number of joints, actuators and sensors required to efficientlyperform motor tasks such as object exploration, manipulation and grasping. The authorsadopt an integrated approach to explore the control of the hand based onsensorimotor synergies that can be applied in both neuroscience androbotics. Hand synergies are based on goal-directed, combined muscle andkinematic activation leading to a reduction of the dimensionality of the motorand sensory space, presenting a highly effective solution for the fast and simplifieddesign of artificial systems.Presented intwo parts, the first part, Neuroscience, provides the theoretical andexperimental foundations to describe the synergistic organization of the humanhand. The second part, Robotics, Models and Sensing Tools, exploits theframework of hand synergies to better control and design robotic hands andhaptic/sensing systems/tools, using a reduced number of control inputs/sensors,with the goal of pushing their effectiveness close to the natural one.Human andRobot Hands provides a valuable reference for students, researchers anddesigners who are interested in the study and design of the artificial hand.